Planning for family succession - Ciprian Domnisoru; Robert Allen Miller (Helsinki Graduate School of Economics, 2025)
Sons succeed their exiting CEO parents more often than daughters. How do entrepreneurial families reach this gender imbalance, and how does it affect the prospects of their firms and their offspring? Using Finnish administrative data on firms linked to population register data on shareholders and their extended families, we trace the steps leading to the succession decision, and its outcomes. We examine fertility patterns, finding evidence of son preference in natural births and adoptions by entrepreneurs. In families that appear to follow son-biased fertility stopping rules, we also find noticeable differences in human capital accumulation between sons and daughters. The transmission of human capital is also mediated by the extent to which women are employed in the industry of the entrepreneur parent. In particular, daughters have a higher chance of being groomed for succession if the family firm operates in a femaledominated industry. Gaps in income, board membership, and share ownership between sons and daughters of exiting CEOs emerge well before succession, and their magnitude also varies by industry gender composition. Turning to firm outcomes, we find evidence that other family members, but not the children of exiting CEOs, appear to diminish firm performance relative to the results of professional CEOs. Overall, our results show family succession is a protracted process that begins with the birth of the first child.
Keywords: G32; L25; J13; J24; 330; Family Firms; Son preference; CEO transition; Gender differences; Human Capital